Nanocomposite based on Gd2O3 nanoparticles and drug 5-fluorouracil as potential theranostic nano-cargo system - Jaroslava Szűcsová; Adriana Zeleňáková; Eva Beňová; Ľuboš Nagy; Martin Orendáč; Veronika Huntošová; Mária Šoltésová; Jaroslav Kohout; Vít Herynek; Vladimír Zeleňák (Heliyon, 2023)
We have prepared silica matrix with hexagonal symmetry of pores (SBA-15) and loaded it with anticancer drug 5-Fluorouracil (5-FU) to promote it as a drug delivery system. Gd2O3 nanoparticles were incorporated into the matrix to enhance nanosystems applicability as contrast agent for MRI, thus enabled this nanocomposite to be used as multifunctional nano-based therapeutic agent. Drug release profile was obtained by UV-VIS spectroscopy, and it indicates the prolongated release of 5-FU during the first hours and the total release after 5 h. The cytotoxicity tests using MTT-assay, fluorescent microscopy, bright-field microscopy, and flow cytometry were carried out using human glioma U87 MG cells and SK BR 3 cells. The nanocomposite with anticancer drug (Gd2O3/SBA-15/5FU) showed toxic behaviour towards studied cells, unlike nanocomposite without drug (Gd2O3/SBA-15) that was non-toxic. Our drug delivery system was designed to minimalize negative effect of Gd3+ ions at magnetic resonance imaging and drug 5-FU on healthy cells due to their encapsulation into biocompatible silica matrix, so the Gd3+ ions are more stable (in comparison to chelates), lower therapeutic dose of 5-FU is needed and its prolongated release from silica pores was confirmed. Very good T1 contrast in MR images was observed even at low concentrations, thus this nanosystem can be potentially used as contrast imaging agent.